2021
DOI: 10.1007/s43546-021-00138-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of remittance and volatility in remittances on macroeconomic performance in Africa: any lessons for COVID-19?

Abstract: Premised on the World Bank’s projection of a 20% fall in global remittances due to the effect of the COVID-19 pandemic, there have been concerns that remittance-dependent countries may be excessively affected. In this study, we explore the link between remittance, remittance volatility and macroeconomic performance to make a case for the potential impact of the COVID-19 pandemic. Specifically, the study examined the impact of remittance volatility on some macroeconomic variables [real gross domestic product (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The findings indicate that remittances exert upward pressure on the real exchange rate. To estimate the possible impact of the COVID-19 pandemic, Awode et al (2021) investigate the links between remittances, remittance volatility, and macroeconomic performance in seven African nations. The authors find that while remittances themselves have a positive and considerable impact on GDP, consumption, and investment in this region, remittance volatility has a negative but negligible influence on exports, exchange rates, and GDP.…”
Section: Nexus Between Remittances and Exchange Ratesmentioning
confidence: 99%
“…The findings indicate that remittances exert upward pressure on the real exchange rate. To estimate the possible impact of the COVID-19 pandemic, Awode et al (2021) investigate the links between remittances, remittance volatility, and macroeconomic performance in seven African nations. The authors find that while remittances themselves have a positive and considerable impact on GDP, consumption, and investment in this region, remittance volatility has a negative but negligible influence on exports, exchange rates, and GDP.…”
Section: Nexus Between Remittances and Exchange Ratesmentioning
confidence: 99%
“…But the empirical link between foreign remittances and reductive or weak growth, increased feelings of economic inequality and deprivation has also been established in the academic literature. Remittances was found to associate with real exchange rate appreciation, net export deficiency, non-tradable consumption, reductive investment, lower labour participation, production market deficiency, inflation, Dutch disease and increased feelings of deprivation (Chami et al 2005 ; Mishra 2005 ; Azam and Gubert 2006 ; Catrinescu et al 2009 ; Acosta et al 2009 ; Lianos and Cavounidis 2010 ; Vacaflores 2012 ; Mokhouf and Mazhar 2013 ; Khan and Islam 2013 ; Ball et al 2013 ; Amuedo-Dorantes 2014 ; Sutradhar 2020 ; Awode et al 2021 ; Imran and Mohammed 2022 ). In another vein, a study by International Monetary Fund, IMF ( 2005 ) on 101 developing countries found no significant relationship between remittances and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this literature review, one could argue that uncertainty (i.e., unpredictability) of remittances inflows would likely be detrimental to remittance-receiving households, and ultimately adversely affect the domestic economy of the recipient country, for example, through lower consumption, lower investment not only on human capital but also on businesses. Existing studies that have examined the macroeconomic effects of remittances inflows uncertainty (or unpredictability) are very limited, and have proxied the unpredictability of remittances inflows by the volatility of these resource inflows (e.g., Amuedo-Dorantes and Pozo, 2014;Awode et al 2021;Opperman and Adjasi, 2018). For example, Amuedo-Dorantes and Pozo (2014) have shown that both the size and the uncertainty of remittances influence (positively) the accumulation of human, physical and financial assets among recipient households in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Opperman and Adjasi (2018) have established empirically that the volatility of remittances inflows is detrimental to both banking sector depth and efficiency, but exerts no significant effect on stock market development in Sub-Saharan African countries. More recently, Awode et al (2021) have uncovered that there is no significant impact of the volatility of remittances inflows on the real gross domestic product, consumption, investment, export, and the real exchange rate.…”
Section: Introductionmentioning
confidence: 99%